Pengaruh Iradiasi Sinar Gamma terhadap Kandungan Flavonoid dan Tanin Total Teh Putih (Camellia sinensis L.) dan Benalu Teh (Scurulla atropurpurea BL. Dans) - Sari, Bina Lohita; Rahayu, Dien Puji; Rohdiana, Dadan; Nurlita, Selvi; Sahara, Putri Siti (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2018)
Camellia sinensis L. leaves, commonly known as white tea, are cultivated from unfurled bud leaves and protected from the sun while were hand picked. Scurulla atropurpurea [BL] Dans is well-known as loranthus of tea. The active compounds of both samples are flavonoid (flavanol, flavonol) and tannin. High humidity conditions can damage the simplicia of medicinal plants in the long-term storage process.The irradiation process with gamma rays can extent the shelf life of simplicia.Gamma irradiation is one of the most effective methods to extend the shelf life of simplicia. Both simplicia were irradiated in room temperature at 60Co source at doses of 0; 2.5; 5; 7.5; 10 and 12.5 kGy. Irradiation simplicia was immediately extracted with microwave assisted extraction (MAE) using 60% ethanol solvent to produce white tea and loranthus of tea extract. Flavonoid and total tannin content were determined using aluminium chloride and folin-ciocalteau methods. Flavonoids and total tannin in the tea samples were 2.56; 2.50; 3.73; 3.14; 2.68; 2.34 mgQE/g and 109.67; 132.87; 149.40; 107.29; 141.82;134.95 mgGAE/g, respectively. Meanwhile in the loranthus of tea were 7.10; 5.68; 5.79; 8.84; 5.01; 5.44 mgQE/g and 60.34; 58.61; 58.59; 71.37; 54.16; 65.99 mgGAE/g, consecutively. Results of the research showed that radiation dose of 5 kGy was found to be effective dose for white tea whilest 7.5 kGy for loranthus of tea to reach highest flavonoid and total tannin content.